2022
DOI: 10.1177/15271544221120205
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Registered Nursing: Influences of Health-Related Work Experience and Education Financing

Abstract: A larger and more diverse registered nurse (RN) workforce in the U.S. is needed to meet growing demand and address social determinants of health and improve health equity. To improve understanding of pathways and barriers to becoming an RN, this study examined prior health care employment and financial assistance factors associated with completion of pre-licensure RN education programs, by initial entry degree (associate degree or bachelor of science in nursing) and across racial and ethnic groups, using the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A study also found that Black and Hispanic nurses were more likely than other students to rely solely on student loans for their initial nursing education versus other sources of financing, such as employer tuition support or federal traineeships and scholarships. 50 Clearly, finances present an obstacle that disproportionately affects the kinds of students needed to diversify the workforce and improve population health. Further harming workers from historically marginalized communities is the pay gap that they experience compared with White peers across skill levels, which may also affect a worker's ability to afford future schooling.…”
Section: Uncertain Career and Education Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…A study also found that Black and Hispanic nurses were more likely than other students to rely solely on student loans for their initial nursing education versus other sources of financing, such as employer tuition support or federal traineeships and scholarships. 50 Clearly, finances present an obstacle that disproportionately affects the kinds of students needed to diversify the workforce and improve population health. Further harming workers from historically marginalized communities is the pay gap that they experience compared with White peers across skill levels, which may also affect a worker's ability to afford future schooling.…”
Section: Uncertain Career and Education Pathwaysmentioning
confidence: 99%
“…These students were more likely to take on loans, and loans of higher amounts, compared to students from public and not‐for‐profit schools. A study also found that Black and Hispanic nurses were more likely than other students to rely solely on student loans for their initial nursing education versus other sources of financing, such as employer tuition support or federal traineeships and scholarships 50 . Clearly, finances present an obstacle that disproportionately affects the kinds of students needed to diversify the workforce and improve population health.…”
Section: Recruiting and Retaining The Workforce That Reflects The Pop...mentioning
confidence: 99%